Relasi Kuasa Etnis Melayu dan Tionghoa Pada Pilkada Kabupaten Bangka Barat 2020 - Hidayat, Novendra; Fatah, Abdul (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
This article aims to examine and understand the power relations that occur between ethnic Malays and Chinese in local political electoral contestation in the Bangka Belitung Islands Province. The location of this research is West Bangka Regency. The phenomenon of the election of Regent and Deputy Regent pairs from Malay and Chinese ethnic groups in the last two Regional Head Elections in West Bangka Regency is the basis for the importance of this research. where previously ethnic Malays always dominated the district's electoral political contestation. West Bangka stands. The article objects are selected Malay and Chinese elites, political parties and winning teams. This article uses political identity theory and modalities in politics. Qualitative descriptive research method with data collection techniques using interviews, documentation and observation. Meanwhile, to select informants using purposive sampling technique. This research concludes that there is a Malay - Chinese (Sukirman and Bong Ming-Ming) happens naturally, the historical traces of these two ethnicities have existed since the opening of this area until it developed to what it is now. These two ethnic groups then strengthen each other in various aspects, both political, economic and socio-cultural. Each ethnic group attempts to exert power by accumulating and mobilizing various forms of capital to maintain or seize social position. In regional election battles, actors (ethnic groups) mobilize all their capital to influence, gain support and seize social positions in society.